Comparative Analysis Of Hammer Test And Compression Testing Machine Against Normal Concrete Compressive Strength Test K300 - Putra Anugrah Pratama, Vicky; Setioningsih, Retnowati; Marwanto, Marwanto (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
The materials used in a concrete construction have a major impact on its strength. But a lot of other things also matter, like the cement-water ratio (FAS), temperature fluctuations, curing conditions, and lack of compaction. The purpose of this study is to evaluate the findings of compressive strength testing of K-300 quality concrete using two different approaches: the non-destructive Hammer Test (HT) and the destructive Compression Test Machine (CTM). Both techniques were used to examine ten cube-shaped concrete samples that were 15 cm x 15 cm x 15 cm. The two approaches differed significantly, according to the results. Compressive strength values ??from CTM were consistently higher than those from HT. Test specimen number 7 showed that CTM had the highest compressive strength at 507.92 kg/cm², while test specimen number 10 showed that HT had the highest compressive strength at 247kg/cm². These findings suggest that in order to get more accurate results, CTM should be used in concrete testing